Pengaruh Lingkungan Keluarga terhadap Kemampuan Literasi Anak Kelas 1 SDIT di Surakarta - Fathia Rahma, Zulfa; Sutanto, Alfiani Vivi; Minropa, Aida (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background: Family is a place for children to grow and develop. The family environment is the oldest educational institution which is informal in nature, which is first and foremost experienced by children as well as natural educational institutions (Wahid, et al., 2020). Literacy is important in child development. Literacy is the absorption of information in the form of knowledge from text and orally, to develop cognitive abilities, through reading and writing (Arsa, et al., 2019). Parents must be able to increase their knowledge and abilities in creating a conducive family environment and conditions to support the child's development process (Framanta, 2020). Objectives: This study aims to determine the influence of the family environment on literacy ability in 1st grade students at Islamic school in Surakarta. Methods: This study used a cross sectional approach. The sampling technique in this study was purposive sampling. The collected data will be analyzed by univariate and bivariate analysis using the Kendall Tau test. Results: The results of bivariate analysis using the Kendall Tau test indicated a p value of 0.000 where p <0.05 which means that the family environment influences literacy skills. Conclusion: The literacy ability of 1st SDIT children can be influenced by the family environment. Keywords: Family Environment, Literacy Skills, Family Environment Factors, Child Development